Is Kauppila method able to detect the progression of vascular calcification and predict cardiovascular events in patients undergoing hemodialysis? - Delatim Vannini, Francieli C. [UNESP]; Teixeira, Altamir Santos [UNESP]; Caramori, Jacqueline C.T. [UNESP]; Martin, Luis Cuadrado [UNESP]; Barretti, Pasqual [UNESP] (Dustri-Verlag Dr. Karl Feistle, 2016)
Background: Cardiovascular disease (CVD) is the main cause of death in hemodialysis (HD) patients. Vascular calcification (VC) is common in these patients. The main objective of this study was to evaluate if a semiquantitative radiographic method is able to detect VC progression in a prospective cohort of patients and predict the risk of cardiovascular events. Secondarily, we intend to identify predictors of the presence and progression of VC. Methods: 49 patients undergoing HD for = 90 days were included. At the beginning and after 12 months, the VC score (VCS) was determined by the Kauppila method, and clinical, nutritional, and laboratory markers were measured. The rates of fatal and nonfatal cardiovascular events were analyzed from months 13 to 24. Results: Of 49 patients, 55.1% were male, 46.9% diabetic, and the mean age was 59.5 ± 14.4 years. At the beginning of the follow-up, 65.3% of the patients exhibited VC with a median VCS of 4 points. The intracellular water was negatively associated with VC and its intensity. The presence of VC was the only independent predictor of VC progression. Among patients with VC, 17 showed rapid progression, and 15 showed slow progression. The VCS was independently associated with rapid progression, while ?VCS (final VCS - initial VCS) was an independent predictor of cardiovascular events. Conclusions: The Kauppila method was able to detect VC, its progression, and predict cardiovascular events. These results suggest an association of VC with nutritional status.
Keywords: Calcium and phosphate metabolism; Cardiovascular; Nutrition; Technical hemodialysis